Formulasi dan Evaluasi Parfum Tipe Eau de Toilette (EDT) “Senarai Jingga” - Indra Gunawan; Pudji Rahayu (Politeknik Kesehatan Tanjung Karang, 2021)
Lack of research on formulation and evaluation of fragrance products (perfumes) in Indonesia and the need to improve the publication and branding of Tanjungkarang Health Polytechnic (Polkestanka) can be done through the development of perfume products according to climate characteristics in Indonesia. This research with quantitative experimental design aims to produce formulas and fragrance products (perfumes) type Eau de Toilette (EDT) that has the equivalent or better quality of branded perfumes on the markets. The Intervention has done by formulating perfume